Вплив соціальних мереж на сучасний бізнес - Глагольєва, В. Є. (ХНУРЕ, 2024)
Modern society and business are unimaginable without the growing popularity of social networks, which attract the attention of millions of people worldwide every year. The most popular social networks at the moment include Facebook, Twitter, Instagram, TikTok, and Telegram. Social networks have not only gained prominence in modern society as a crucial communication and entertainment channel but have also become an integral component of contemporary business. The impact they exert is multifaceted, ranging from increasing brand visibility and attracting customers to the ability to analyze market trends in real-time.
Keywords: вплив соціальних мереж; сучасний бізнес